Karakterisasi Nanopartikel dan Uji Antiagregasi Platelet Secara In-Vitro terhadap Ekstrak Rumput Laut Coklat (Sargassum polycystum) Hasil Hidrolisis Enzim Sellulase - Kartiningsih Kartiningsih; Syamsudin Abdillah; Partomuan Simanjuntak; Cyntia Cyntia; Haryo Haryo (Fakultas Farmasi Universitas Pancasila, 2019)
Brown seaweed contains fucoidan, a large molecular weight sulfate polysaccharide (about 100,000 Da) which has platelet antiagregation activity. This activity is achieved if the fucoidan has a small molecular weight (3900-7600 Da) so this activity can increase by hydrolized with sellulase Enzym. The purpose of this study was to obtain extract nanoparticles that meet physical quality requirements and have a higher platelet antiagregation activity than brown seaweed extract both before and after hydrolysis. Extraction was using kinetic maseration method using 80% ethanol after that using 2% calcium chloride solution. The results were dried and hydrolyzed with cellulase enzyme and nanoparticles were made by ionic gelation method. Nanoparticle characterization results in particle size of 552.8, polydispersity index of 0.569, potential zeta of +53.5 mV, and spherical shape. In-vitro testing results for platelet antiagregation activity showed the percentage of platelet aggregation inhibition of brown seaweed extract with a concentration 500µg / mL is 22.19% and extracts after hydrolysis was 57.94% and nanoparticles extract after hydrolysis was 72.93%. Extract nanoparticles meet physical quality requirements and extracted nanoparticles after hydrolysis have the highest platelet antiagregation activity compared to brown seaweed extract both before and after hydrolysis.